Cultivating the In-Between: Sponsors, Growers, and the Cultural Landscapes of Urban Agriculture in Contemporary Chicago - (:unkn) unknown (My University, 2024)
This dissertation theorizes a model for understanding agricultural land in an urban setting and ways of “seeing” landscape in depth and beyond only the visual. The model is based on how interstitial urban spaces – spaces inserted between intersecting infrastructural elements or as temporary installations between phases of development - are occupied and transformed into influential urban agricultural sites. I found that the two types of interstitial sites reflect and ultimately reproduce the objectives and practices of sponsors and growers beyond the bounds of an individual place. Urban agriculture has been characterized as consisting of spaces of learning, of community building, of resistance, or of neoliberal policy effects. Likewise, interstitial urban sites have been examined from the perspective of their roles as placeholders, emerging, ephemeral, or temporary spaces in service of development or natural systems. However, the intersection of these two bodies of literature is largely uninvestigated, especially in terms of characterizing the influence that agriculture taking place in interstitials can have on surrounding areas. My dissertation addresses this thinner area of scholarship in spatial influence of urban agriculture by shifting perspective: rather than studying social program as an end, this work contemplates program motivation as part of a collection of forces defining a space and its longer-term influence on other, nearby spaces. Urban agriculture has often operated on the margins, co-opting otherwise unused spaces; this dissertation theorizes two types of urban agricultural sites, spatial and temporal interstitials, as ways to characterize these spaces. My work describes the landscapes that result from sponsor and grower objectives and finds how urban agriculture’s presence affects engagement with food cultivation beyond these interstitial spaces. Different site types have different influences on their surroundings, with temporal interstitials being dispersive, releasing behaviors and knowledge, while spatial interstitials are more often attractive, inviting non-participants to site to learn and experience spaces of agriculture. My research relies on archives, contemporary publications, interviews, and a detailed method of embodied site analysis to trace the advent and possible erasure of urban agricultural sites. I investigated factors that contributed to their durability and diffusion impact. Two sets of case studies illustrate the interstitial models and the possibility of transformation from one type to another while highlighting similarities in how sponsor and grower values become written in the landscape and dispersed beyond the site borders. The theoretical model developed from my field work proposes that interstitial spaces of urban agriculture release an energy in the form of the entangled values of sponsors and growers across a larger population than those directly engaged in cultivation. This influence is observed in expanded or satellite sites that attract new users, neighbors, and programs enhancing local knowledge and collaboration. This research ties together the cultural landscapes of urban agriculture with the decisions about site location, program and participants and shows how these decisions result in different types of interstitial agricultural spaces with differing impacts on their surroundings.